2009
DOI: 10.1177/030089160909500223
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Regression of Two Giant Basal Cell Carcinomas in a Single Patient after Incomplete Excision

Abstract: We present a patient with two independent giant basal cell carcinomas over the left clavicle and the lower back, measuring 7 x 12 cm and 18 x 20 cm, respectively. Both tumors were excised incompletely (R2) and the patient refused followup resections. After 52 and 16 months, respectively, no signs of recurrence were observed. CONCLUSION; Incompletely excised giant basal cell carcinomas can regress spontaneously. A watch-and-wait approach after incomplete resection may be pragmatic to avoid mutilating follow-up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Our study demonstrated an association between CD3ε, CD25, CD68, and ICAM-1 mRNA levels in BCC tumor biopsies and the risk for subsequent tumors. These results support an important role for inflammatory cells in the peri-tumoral milieu and for immune cells that infiltrate BCC tumors and thus mediate BCC tumor progression [12], [13], [20].…”
Section: Discussionsupporting
confidence: 67%
“…Our study demonstrated an association between CD3ε, CD25, CD68, and ICAM-1 mRNA levels in BCC tumor biopsies and the risk for subsequent tumors. These results support an important role for inflammatory cells in the peri-tumoral milieu and for immune cells that infiltrate BCC tumors and thus mediate BCC tumor progression [12], [13], [20].…”
Section: Discussionsupporting
confidence: 67%
“…Though many risk factors for GBCCs are similar to those for BCCs (e.g., Caucasian race, prior history of BCC, and exposure to ultraviolet radiation), a distinct feature of GBCC is a patient's neglect of the lesion and a resulting delay in effective intervention [3, 5, 8, 9]. …”
Section: Discussionmentioning
confidence: 99%
“…A common trend among cases of GBCC is patients’ distrust of contemporary Western medicine [3, 5, 8]. Previous case reports of multiple GBCCs also described patients with established beliefs in holistic or religious treatments [3, 5, 8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations